Effect of feed rate and depth of cut on face milling process on surface roughness of Al-Mg alloy using CNC milling machine 3 axis - Achadiah, Rachmawati; Setyarini, Putu Hadi; Pambayoen, Mas Ayu; Djunaidi, Irfan H.; Azizah, Siti (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The purpose of this study was to determine the effect of feed rate and depth of cut on the surface roughness of Al-Mg aluminum using a DIY CNC Milling Machine and Krisbow Universal Milling Machine as a comparison. The open-loop control system is a control system used in the design of DIY CNC Milling machines. A PC with Mach3 software is used as a PC Based Direct Digital Controller to control the system. In this study, the feed rate variation 24 mm/minute and 42 mm/minute and depth of cut 0.25 mm, 0.5 mm, and 0.75 mm were used. After the face milling process, the surface roughness test was carried out using the Mitoyo Surface Roughness Tester to determine the level of surface roughness of the machining results the DIY Milling Machine and Krisbow Universal Milling Machine as a comparison. The results showed that as the feed rate and depth of cut increased, the surface roughness values of both tools increased.